Empirical Determinants of Corruption in Honduran Municipalities. (30th November 2022) - Bastida, Francisco; Estrada, Lorenzo; Nurunnabi, Mohammad
Abstract: This article evaluates municipal bureaucratic corruption in Honduras on a sample of 268 observations of Honduran municipalities surveyed by the Latin-American Public Opinion Poll for 2004–2016. This bureaucratic corruption is measured by officials' request for a bribe from citizens to get some municipal paperwork done. Financial factors do not impact corruption. Officials could take advantage of citizens' imperfect information (agency problem) to obtain personal benefits and extract income through certain expenditures that allow them to hide corruption. In this regard, Supreme Audit Institution audits refrain officials from incurring corrupt practices by counteracting the agency problem. Accordingly, audit reports should be presented to the municipal council and citizens through open councils. Implementation of digital government would contribute to curbing corruption, as it would minimize officials' contact with citizens and, consequently, bribery.